Methodological Problems of Teaching Arabic to Non-Native Speakers in Indonesia - Ilham Mukhtar; Jamal Fauzi (International Islamic Schools Alliance, 2020)
The Arabic language is a decent place in Indonesian society because it is a religious language that coincided with the entry of Islam in this country. The growing interest in it through the ages and continued to try to raise its status continuously until the field of education witnessed a remarkable development in the last decade. However, this status does not necessarily mean that this language has received what it deserves as a religious and foreign language from the engineering and policy of advanced education. The current status of Arabic language education in Indonesia is a transitional phase, as some promising developments are beginning to take place on the one hand, and it is still facing a number of thorny problems on the other. The teaching of Arabic in most institutes in Indonesia is done in a way that explains the rules and the translation of texts into the Indonesian language. In addition, the evaluation system used to measure the learner's linguistic achievement is largely focused on linguistic aspects. The teaching of Arabic language on such a method is a traditional trend and it has to be changed and developed, and since some of the significant shortcomings related to the curriculum, it requires searching for the places of this deficiency in the curriculum of teaching Arabic in the institutes. The framework of the study is determined in the problems of the curriculum of the Arabic language in terms of objectives, content, method and means of education and evaluation. The study will take its place in the language institutes of the Asia Muslims Charity Foundation (AMCF) in Indonesia.